Biogenic approach for fabricating biocompatible carbon dots and their application in colorimetric and fluorometric sensing of lead ion. (10th January 2021) - Chauhan, Pooja; Chaudhary, Savita; Kumar, Rajeev
Abstract: The rapid growth in the industrial and urban sector has filled enormous stress on environment. The exponential use of chemicals especially metal ions has raised the pollution index and affected the health of living beings. Therefore, it is highly essential need to monitor and remove these metal ion toxins by the advanced materials which itself non-lethal, bio-congenial and easily workable with high selectivity and sensitivity. To solve these issues, the current study proposed the efficient utilization of Pearl Millet seeds into value-added carbon dots (C-dots) via using simple thermal treatment. Engaging agricultural product as a starting precursor for C-dots synthesis made the process economically more viable. The basic structural properties (size ∼ 4–5 nm, shape ∼ spherical, and crystalline nature) were assessed through HRTEM, PXRD, FTIR and EDX analysis. The optical and luminescence properties were appraised by investigating the variation in the absorbance and emission intensity as a function of pH (2–12) and excitation wavelength (245 nm–305 nm). The developed strategy has provided the better control over the aqueous solubility, quantum yield (52%) and optical properties of C-dots. The high loading amounts of C-dots ranging from 100 to 5000 mg/L has produced a significant enhancement in the biocompatibility rate of C-dots against bacterial strains, fungus, algae, chromosomal compatibility on Allium cepa and seeds germination activity of Vigna radiate . The strong fluorescence emission and optical properties of as prepared C-dots made them efficient for selective and sensitive detection of Pb 2+ ion (detection limit = 0.18 nM) from waste water via using colorimetric, UV–vis. absorption and fluorescence based sensory methods. The development sensor performed well in water obtained from different natural resources with 90% average recovery rate. These findings would make the economically feasible C-dots as an effective material for wastewater treatment via overcoming the barriers of low selectivity and advanced the implementation of the process on large scale. Furthermore, the usage of biowaste as starting precursor offers a solution for ecological burdens while synchronically reducing the pernicious effect of the waste on the ecosystem and cleans up the environment. Graphical abstract: Image 1 Highlights: Economically viable method was used for the fabrication of biogenic Carbon dots (C-dots) using Pearl Millet. The antibacterial, antifungal, anti-algal and anti-proliferative activities of C-dots were determined. Allium cepa chromosomal assay was used to explore the genotoxic assessment of C-dots. Promising material for detecting colorimetric and fluorescence-based response for lead ion at nanomolar level.